Penelitian pembuatan kompon PVC untuk acuan sepatu dengan variasi serat pohon pisang - Siti Rochani (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1986)
DOP (Dioctyl Phtalate) is a chemical substance which its function as plasticizer in PVC compound preparation, while the function of fibre of banana stem (musaceae) is a filler. The used of banana stem in this research can improve impact resistance of the compound as well.So the addition of DOP and fibre of banana stem influnces the properties of impact resistance and hardness.The optimum value of impact resistance (23,12 kgcm/cm) is archived by the PVC compound which using DOP 50% and banana stem 40%, and the optimum value of hardness (65 shore D) is achived by using DOP 30% and banana stem 50%.